A Brief Survey Onboolean Expressions in Fault Based Techniques - Sivaranjani, M; Devi, D.Gayathri Devi (International Journal of Computer Sciences and Engineering, 2025)
Boolean expressions are major focus of specifications and they are very much prone to introduction of faults, this survey presents various fault based testing techniques.It recognizes that the methods differ in their fault detection capabilities and creation of test suite. The various techniques like Dealing with Constraints in Boolean Expression, Minimal Fault Detecting Test Suites, Reducing logic test set size, A logic mutation approach, SAT and SMT Solvers for Test Generation and Boolean Expressions by Cell Covering has been considered. This survey describes the fundamental algorithms and fault categories used by these strategies for evaluating their performance. Finally, it contains short summaries of the papers that use Boolean expressions used to specify the requirements for detecting faults. These techniques have been empirically evaluated by various researchers on a simplified safety related real time conditionals system